Kunumi Rukara: uma etnografia dos terreiros de criança Asuriní - Miranda, Xanda de Biase (2014)
The dissertation deals with how the Asurini from the Xingu conceive and produce their children and how their children portray themselves and the reality they see. The images of the fieldwork brought to the theoretical field, reveal the relationship between spaces, knowledge and skills, managed by men and women in manufacturing consanguineous bodies, prepared by and for the shamanism. It also approaches the matter of mobility of the groups of children in the space delimited from the ukara (yard), whitch serves as a cutting to the sociality, giving to each child the possibility of activate alternatively a net of relationships with people of its age group and/or genre, defined from the matrilineal or patrilineal branch. The remaining possible relationships out side of the ukara exist in the context of affinity and are built from the oppositions and contradictions. The debate about the importance of the kwasiat knowledge, term which designates as much the geometrical drawings as the writing, opens and closes the work, characterizing at the same time a representative visual code, a prophylactically art and a Assurini way of comprehension of the writing, which determines the place of the school education and highlights the complexity of the notion of “bilingualism and interculturalism” in this field.